The influence of the roles of mobile-phone users on the adoption of m-commerce activities the case of Kenya - Machoka, Philip Gichaba (Department of Information Systems, 2023)
Mobile technologies arrival and phenomenal growth have moved the boundaries of how business transactions are conducted today, i.e., the emergence of mobile commerce (m-commerce). Mcommerce presumes mobility, broad reach, ubiquity, convenience, and localization of devices and users. As a result, M-commerce is also transforming conventional value networks and the broader countries' economies. Understanding what drives m-commerce adoption in developing economies remains unclear because of competing/conflicting findings in m-commerce adoption studies. Little is known about the roles mobile-phone users play, i.e., technology-user role, consumer role, social network-member role, and how they influence the adoption of m-commerce activities (i.e., content delivery, entertainment, and transactions). Mobile-phone users are individuals using mobile-phone devices for communication, transactions, entertainment, and socialization. This study defines roles as the part people play in performing day-to-day social life. Therefore, this study seeks to identify factors influencing mobile-phone users towards adopting m-commerce activities from mobile-phone users roles viewpoint. A review of information systems literature revealed that mobile-phone users play the following roles: technology-user, consumer, and social network-member. A literature review also revealed a dearth of empirical studies focusing on adopting and accepting m-commerce in developing economies compared to western ones. This study further combined theories within and across disciplines to develop an integrated m-commerce activities adoption model. Integrating theories and models allows accounting for phenomena that neither can address independently. Therefore, technology adoption theory, consumer decision-making styles model, and social network theories guided this study and developed the study's conceptual model. Unlike previous studies, which focused on whether individuals adopted m-commerce or not, this study looked at mcommerce adoption more broadly from the activities individuals engage in (i.e., content delivery, transactions, and entertainment). A conceptual model was developed and empirically tested. Structural equation modeling (SEM) analysis revealed that mobile-phone users' roles as technology-users, consumers, and social network-members influence the adoption of mcommerce activities. The significant theoretical contribution of this study is the development of a conceptual model. This model provides a more comprehensive understanding of the adoption determinants that influence mobile-phone users' intentions and decisions towards adopting m-commerce activities from the perspective of their roles using mobile-phones. This research addresses the knowledge gap that exists in m-commerce adoption in developing economies literature. Furthermore, the approach utilized in the present study contributes to the multi-disciplinary approach to IS inquiry by drawing on concepts and theories from reference disciplines. Likewise, the study results have implications for practice. First, the study underscored the significance of the roles of mobile-phone users as they engage with mobile technologies. In addition to mobile-phone users being technology users who engage with complex technology while conducting m-commerce activities, m-commerce providers, developers, and designers need to be cognizant that mobile-phone users are consumers. They pay and make purchaserelated decisions when they engage in m-commerce activities. Furthermore, mobile-phone users are also social network-members who engage with other network members, influencing them to adopt a technology. Therefore, familiarity by m-commerce providers, developers, and designers with mobile-phone users' roles while performing m-commerce activities is essential. This allows the development and deployment of suitable m-commerce solutions, bearing in mind the roles individuals play when using mobile-phone devices. Future studies should look at how different types of m-commerce activities (content delivery, transactions, and entertainment) are specifically appropriated and used. For example, what specific entertainment activities do mobile-phone users engage in, such as streaming movies, listening to music, and playing online games? In what way are these specific entertainment activities appropriated and used? This can provide a better understanding of how the specific activities are adopted and used. Users' demographics are used to segment markets. It will also be important to understand how users' demographics influence the adoption of m-commerce activities. Future studies can also test this model in other developing countries. Last but not least, this study may not have considered other significant variables, and future studies may include other variables to improve the model further.